Effects of Sago Pith Waste Compost and Young Coconut Water Treatment On Nutmeg (Myristica fragans Houtt) Seedling Gowth In Nurseries - Saiti Maryam Lestaluhu; Johan Riry; Maimuna La habi (Agrologia, 2022)
Nutmeg (Myristica fragans Houtt) is one of the plantation crops that has high economic value in addition to cloves, rubber, coffee, tea and cocoa. To get good plant growth, quality seeds are needed and to get good seeds, sufficient nutrients are needed for the growth of roots, stems and leaves. Planting media in nurseries must be of good quality so that the seeds produced are also of good quality, one of the quality planting media is using sago ela compost and using young coconut water as a growth regulator. This study aims to obtain the optimal dose of sago ella compost and young coconut water concentration on the growth of nutmeg seedlings in nurseries. The treatments used sago ella at a dose of 300 g/pot and 600 g/pot), and young coconut water with concentrations of 0%, 25% and 50%. The results showed that the sago ella treatment had a significant effect on the variables of plant height, leaf number and root length, but had no effect on stem diameter and root crown ratio, while young coconut water treatment had an effect on seedling height and number of leaves, but had no effect on root length. , stem diameter and crown to root ratio. The real interaction was only on plant height